Pragmatic Analysis of Advertising Slogans from the Perspective of Politeness Principle - Zhang, Jiayue (Journal of Theory and Practice in Linguistics, 2024)
Politeness is the traditional virtue of the Chinese nation, and it is also a moral principle that people should generally abide by. This paper by using Leech’s politeness principle and taking advertising slogans as the research object, to explore how to use the politeness principle to realize the artistry of advertising slogans, in order to stimulate consumers’ desire to buy goods, and to achieve the desired purpose of advertisers.